The Incidence of Trypanosoma cruzi in Triatoma of Tucson, Arizona - Bice, David E. (1966)
Species of Triatoma rubida uhleri and T. protracta were collected and dissected to determine the percentages infected with Trypanosoma cruzi from areas near Tucson, Arizona. Of 657 T. rubida uhleri and T. protracta dissected 65 (9.9 per cent) were infected. When each species was considered separately, a higher infection rate was found in T. protracta than in T. rubida uhler; (19.5 per cent compared to 7.5 per cent), even though there were a higher number of T. rubida uhleri observed in the field. One area was found with a significantly higher infection rate of 19.2 per cent, compared to 2.9 per cent from all other areas.A seasonal pattern for the occurrence of T. rubida uhleri instars during the year was noted. The adults were found in May and June, 1st, 2nd, 3rd and 4th instars developed through the summer months, and by the end of September the majority of T. rubida uhleri collected were 5th instars. The 5th instars molted in the spring to the adult stage.